2012
DOI: 10.3109/09273948.2011.628432
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Immunological and Inflammatory Components in Age-related Macular Degeneration

Abstract: Age-related macular degeneration (AMD), affecting 30 to 50 million elder individuals worldwide, is a disease affecting the macular retina and choroid that can lead to irreversible central vision loss and blindness. Recent findings support a role for immunologic processes in AMD pathogenesis, including generation of inflammatory related molecules in the Bruch’s membrane, recruitment of macrophages, complement activation, microglial activation and accumulation in the macular lesions. Pro-inflammatory effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 114 publications
0
59
0
1
Order By: Relevance
“…Many cells of the innate and adaptive immune system, including mast cells, macrophages, and lymphocytes, have been found in macular lesions and the adjacent choroid area [7,8]. Furthermore, genetic polymorphisms in many immune-related genes have been associated with altered AMD risk [9]. Together, these results suggest that dysregulation in the immune system may contribute to AMD progression, but the mechanistic details remain to be established.…”
Section: Introductionmentioning
confidence: 86%
“…Many cells of the innate and adaptive immune system, including mast cells, macrophages, and lymphocytes, have been found in macular lesions and the adjacent choroid area [7,8]. Furthermore, genetic polymorphisms in many immune-related genes have been associated with altered AMD risk [9]. Together, these results suggest that dysregulation in the immune system may contribute to AMD progression, but the mechanistic details remain to be established.…”
Section: Introductionmentioning
confidence: 86%
“…Choroidal neovascularization (CNV), the hallmark of wet AMD, was shown to be dependent on inflammatory cytokines, as well as inflammatory signals. Genetic studies also demonstrated strong associations between AMD and several gene variants in genes coding for inflammatory mediators and complement proteins (1)(2)(3).…”
mentioning
confidence: 99%
“…Genome-wide linkage analyses and candidate gene-based association studies have suggested and identified several chromosomal regions that may appear to contribute to AMD susceptibility [37,38,39]. To date, both 1q15–32 and 10q26 loci are the most strongly associated with disease [40]. Several independent studies have reported that a Y402H polymorphism in the CFH gene makes a substantial contribution to disease susceptibility with OR for AMD ranging between 2.4 and 4.6 for carriers of the H allele and between 3.3 and 7.4 for HH homozygotes [18,41,42].…”
Section: Discussionmentioning
confidence: 99%